Phytoconstituent Analysis and Antibacterial Potential of Epicarp Extracts from Mature Fruits of Persea americana Mill - Cyuzuzo Callixte; Dusabimana Jean Damascene; Anwar Ma'aruf; Yoes Prijatna Dachlan; Anggraini Dwi Sensusiati; Ndayisaba Daniel; Eka Nora Vitaloka Aprilia Putri Winthoko (Cell and BioPharmaceutical Institute, 2020)
Background: World Health Organization (WHO) has reported the antimicrobial resistance as one among the ten threats to global health in 2019. The development of plant-derived antibiotics is currently considered as a modern medicine’s greatest success. Persea americana is a plant with high medicinal profile which allow its different parts to be used for therapeutic purposes. This study is aimed to determine the antibacterial potential of ethanol and chloroform extracts from epicarp of mature fruits of P. americana Mill against human pathogens.Materials and Methods: The epicarps of avocado were dried in oven and ground into powder using porcelain mortar and pestle. The powdered plant materials were extracted with both 96% ethanol and chloroform. Extracts were qualitatively screened to examine their bioactive contents and agar well diffusion method was used to analyze the antibacterial activity of extracts against both Gram-positive and Gram-negative bacteria.Results: Both solvents showed the ability to dissolve the secondary metabolites from avocado epicarps. Phytochemical screening disclosed the presence of alkaloids, proteins, terpenoids, tannins, flavonoids, steroids and phenolic compounds in ethanolic extracts and absence of flavonoids and tannins in chloroform extracts. The extracts showed the inhibition zones ranging from 14±4.5 mm to 26±2.1 mm while streptomycin demonstrated high inhibition zones ranging from 20±3.1 mm to 30 mm. The minimum inhibitory concentration (MIC) values of extracts ranges from 0.3125 mg/mL to 20 mg/mL while the MIC values for streptomycin vary from 0.25 mg/mL to 1.25 mg/mL.Conclusion: The ethanol and chloroform extracts proved to be potentially effective as natural alternative preventives to fight against various disease-causing bacteria.Keywords: antibacterial activity, ethanol extract, chloroform extract, Persea americana, Rwanda